2014
DOI: 10.1007/s10482-014-0248-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus haikouensis sp. nov., a facultatively anaerobic halotolerant bacterium isolated from a paddy soil

Abstract: A Gram-stain positive, rod-shaped, endospore-forming and facultatively anaerobic halotolerant bacterium, designated as C-89(T), was isolated from a paddy field soil in Haikou, Hainan Province, People's Republic of China. Optimal growth was observed at 37 °C and pH 7.0 in the presence of 4% NaCl (w/v). The predominant menaquinone was identified as MK-7, the major cellular fatty acids were identified as anteiso-C(15:0) and iso-C(15:0), and the major cellular polar lipids were identified as phosphatidylethanolami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This species is a known endophytic bacterium (Han et al, 2011), shown to trigger an increase on monoterpenes, sesquiterpenes, tocopherols, and membrane sterols, compounds engaged in antioxidant capacity in leaf tissues of grape resulting in stress tolerance (Salomon et al, 2016). Bacillus haikouensis is halotolerant bacterium isolated from paddy soil, able to grow on up to 17% NaCl (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is a known endophytic bacterium (Han et al, 2011), shown to trigger an increase on monoterpenes, sesquiterpenes, tocopherols, and membrane sterols, compounds engaged in antioxidant capacity in leaf tissues of grape resulting in stress tolerance (Salomon et al, 2016). Bacillus haikouensis is halotolerant bacterium isolated from paddy soil, able to grow on up to 17% NaCl (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This species is a known endophytic bacterium ( Han et al, 2011 ), shown to trigger an increase on monoterpenes, sesquiterpenes, tocopherols, and membrane sterols, compounds engaged in antioxidant capacity in leaf tissues of grape resulting in stress tolerance ( Salomon et al, 2016 ). Bacillus haikouensis is halotolerant bacterium isolated from paddy soil, able to grow on up to 17% NaCl ( Li et al, 2014 ). Oceanobacillus picturae is a halophilic phosphate-solubilizing species with demonstrated siderophore production potential, isolated from saline environments and shown to promote plant growth in mangroves and confer salinity stress tolerance in barley ( El-Tarabily and Youssef, 2010 ; Mapelli et al, 2013 ; Orhan and Demirci, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This species is a known endophytic bacterium [44], that has been shown a systemic response that trigger an increase on monoterpenes, sesquiterpenes, tocopherols and membrane sterols, compounds engaged in antioxidant capacity in leaf tissues of grape resulting in stress tolerance [45]. Bacillus haikouensis is a recently described halotolerant bacterium isolated from paddy soil, able to grow on up to 17% NaCl concentrations [46]. Oceanobacillus picturae is a halophilic phosphate-solubilizing species with demonstrated siderophore production potential that has been isolated from saline environments and has been shown to promote plant growth promotion in mangroves and confer salinity stress tolerance in barley [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…(National Center for Biotechnology Information, Bethesda, MD, USA) and MEGA version 5.0 after multiple alignments. 56 Clustering was performed with the neighbor-joining method, and the phylogenetic tree was determined using bootstrap analysis based on 1200 resamplings. 13 C-DNA.…”
Section: Cultivation Of Active Toluene Degraders Bymentioning
confidence: 99%